2017
DOI: 10.1038/nphys4105
|View full text |Cite
|
Sign up to set email alerts
|

Experimental realization and characterization of an electronic Lieb lattice

Abstract: Geometry, whether on the atomic or nanoscale, is a key factor for the electronic band structure of materials. Some specific geometries give rise to novel and potentially useful electronic bands. For example, a honeycomb lattice leads to Dirac-type bands where the charge carriers behave as massless particles [1]. Theoretical predictions are triggering the exploration of novel 2D geometries [2–10], such as graphynes, Kagomé and the Lieb lattice. The latter is the 2D analogue of the 3D lattice exhibited by perovs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
347
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(355 citation statements)
references
References 40 publications
6
347
1
1
Order By: Relevance
“…Our findings might open a new pathway in the attempts to realize the most suitable environment and conditions for full control of the light propagation in photonics. Some experimental realizations of electronic Lieb lattices have also been done recently using CO molecules on Cu(111) [50]. The proposed system may be a good candidate for our predictions, since it allows one to tune parameters that cannot be easily varied in a real solidstate material.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings might open a new pathway in the attempts to realize the most suitable environment and conditions for full control of the light propagation in photonics. Some experimental realizations of electronic Lieb lattices have also been done recently using CO molecules on Cu(111) [50]. The proposed system may be a good candidate for our predictions, since it allows one to tune parameters that cannot be easily varied in a real solidstate material.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Qiu et al showed that the artificial Lieb lattices can be realized on the metallic copper surface 13 . The artificial Lieb Lattice was rapidly confirmed in experiments 14,15 , providing a realistic electronic Lieb lattice system to explore the above-mentioned physics.…”
Section: Introductionmentioning
confidence: 88%
“…1. The noninteracting 2D Lieb lattice has been realized using ultracold atoms [17,26], photonic lattices [27,28], and also electronically [29,30]. To explore flat-band ferromagnetism, the repulsive Hubbard model on the 2D Lieb lattice has previously been studied using real-space dynamical mean theory (R-DMFT) combined with a numerical renormalization group (NRG) impurity solver at half-filling and zero temperature [6].…”
Section: Introductionmentioning
confidence: 99%